PENGARUH LOVE OF MONEY, EQUITY SENSITIVITY, DAN MACHIAVELLIAN TERHADAP PERSEPSI MAHASISWA MENGENAI TAX EVASION - Fatihah, Helmalya; Murni, Siti Asiah (POLITEKNIK LP3I JAKARTA, 2023)
The research aims to analyze Love of Money, Equity Sensitivity and Machiavellian towards the perceptions of accounting students at Wijaya Kusuma University, Surabaya regarding tax evasion. This study uses quantitative methods and data collection procedures are used by administering questionnaires, while the sample uses purposive sampling. The analysis technique uses multiple linear regression analysis. The research results show that love of money, equity sensitivity and Machiavellian influence students' perceptions regarding tax evasion. Keywords: Love of Money, Equity Sensitivity, Machiavellian, Tax Evasion